2017
DOI: 10.22271/ortho.2017.v3.i4a.05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcome of treatment of idiopathic clubfoot by ponseti technique of manipulation and serial plaster casting

Abstract: Idiopathic clubfoot or congenital talipes equinovarus is the commonest congenital foot deformities having 1 in every 1000 children born worldwide. Around 80% of the cases occur in developing nations. It remains the most difficult to treat. The most widely used treatment is the Ponseti method of manipulation and serial plaster followed by an Achilles tenotomy. This method is effective in 90% of all cases. The objective of this study was to evaluate the outcomes of the Ponseti manipulation and casting method in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…The newborns that received early intervention for congenital clubfoot improved only with conservative treatment. All the families were satisfied with the use of EVA when asked about the appearance of their newborn's foot, corroborating the results of Kumar, Suman and Manjhi (2017) and Kulambi et al (2017) These authors consider the conservative treatment a positive method for resolving the deformity and report that parents were satisfied with the appearance of their newborn's foot. Both describe the evolution of CC in pediatric patients after conservative treatment and serial plaster casting.…”
Section: Discussionsupporting
confidence: 73%
“…The newborns that received early intervention for congenital clubfoot improved only with conservative treatment. All the families were satisfied with the use of EVA when asked about the appearance of their newborn's foot, corroborating the results of Kumar, Suman and Manjhi (2017) and Kulambi et al (2017) These authors consider the conservative treatment a positive method for resolving the deformity and report that parents were satisfied with the appearance of their newborn's foot. Both describe the evolution of CC in pediatric patients after conservative treatment and serial plaster casting.…”
Section: Discussionsupporting
confidence: 73%
“…In Azimi and Narouie's study of 32 clubfeet, the mean Pirani score dropped from 5.53 to 0.09 after 4 to 14 months of treatment, which was to be expected, given the scoring shortly after treatment [13]. Kumar et al have also reported a decrease in mean Pirani score from 5.3 to 0.8 following six to twenty months of Ponseti management [22].…”
Section: Discussionmentioning
confidence: 86%
“…Estratégias conservadoras são promissoras para o tratamento do pé torto congênito postural. 3,23,24 Além disso, o telemonitoramento oferece uma oportunidade única para o engajamento ativo dos pais durante o tratamento. Também serve como uma alternativa essencial para incentivar a participação da família e monitorar seu papel no cuidado e reabilitação de crianças com diversas condições de saúde, promovendo um senso de apoio e vínculo mesmo quando estão fisicamente distantes dos serviços de saúde.…”
Section: Discussionunclassified